2006
DOI: 10.4161/rna.3.1.2789
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Non-Protein-Coding Transcripts from Protein-Coding mRNA

Abstract: Several recent studies indicate that mammals and other organisms produce large numbers of RNA transcripts that do not correspond to known genes. It has been suggested that these transcripts do not encode proteins, but may instead function as RNAs. However, discrimination of coding and non-coding transcripts is not straightforward, and different laboratories have used different methods, whose ability to perform this discrimination is unclear. In this study, we examine ten bioinformatic methods that assess prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 37 publications
1
87
0
1
Order By: Relevance
“…The most widely accepted method for distinguishing protein-coding and noncoding RNAs among novel transcripts is analysis of the length of the open reading frames (ORFs) in each transcript as the primary criterion, followed by determination of the level of phylogenetic conservation of ORFs in transcripts that are classified as noncoding by the use of the first criterion. Since the majority of annotated eukaryotic proteins are longer than 100 amino acids, in most studies, RNAs that lack an ORF of 300 nt or longer have been classified as putative noncoding RNAs (Frith et al 2006a;Clamp et al 2007;Dinger et al 2008). However, there are several bona fide eukaryotic proteins that are shorter than 100 amino acids, and it has been suggested that they may be much higher in number than previously thought (Frith et al 2006b).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The most widely accepted method for distinguishing protein-coding and noncoding RNAs among novel transcripts is analysis of the length of the open reading frames (ORFs) in each transcript as the primary criterion, followed by determination of the level of phylogenetic conservation of ORFs in transcripts that are classified as noncoding by the use of the first criterion. Since the majority of annotated eukaryotic proteins are longer than 100 amino acids, in most studies, RNAs that lack an ORF of 300 nt or longer have been classified as putative noncoding RNAs (Frith et al 2006a;Clamp et al 2007;Dinger et al 2008). However, there are several bona fide eukaryotic proteins that are shorter than 100 amino acids, and it has been suggested that they may be much higher in number than previously thought (Frith et al 2006b).…”
Section: Introductionmentioning
confidence: 97%
“…Rather, the term ''long'' and an arbitrary lower size limit of 200 used in many studies mainly serve to distinguish these transcripts from the small housekeeping or regulatory RNAs such as the snRNAs, snoRNAs, tRNAs, or the miRNAs and other Ago-associated small regulatory RNAs. Similarly, there are no clear-cut, uniformly used criteria for determining the noncoding character of an RNA (Frith et al 2006a;Clamp et al 2007;Dinger et al 2008). The most widely accepted method for distinguishing protein-coding and noncoding RNAs among novel transcripts is analysis of the length of the open reading frames (ORFs) in each transcript as the primary criterion, followed by determination of the level of phylogenetic conservation of ORFs in transcripts that are classified as noncoding by the use of the first criterion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several lines of evidence have accumulated in the last five years suggest that a diverse population of non-protein-coding RNAs (ncRNAs) may be a key player as well. Projects aimed at generating a full catalogue of human and mouse cDNAs have identified at least several thousand polyadenylated transcripts that contain no predicted open reading frames (ORFs) and that are conserved even in very closely related species (Carninci et al, 2005;Frith et al, 2006;Furuno et al, 2006;Carninci and Hayashizaki, 2007). Many of these ncRNAs are spliced, 5Јcapped and transcribed by RNA polymerase II, thus resembling mRNAs in every way except for the fact that they do not appear to code for proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of protein-coding potential of mouse and human Sox2ot/SOX2OT full-length cloned sequences with the software CRITICA, which uses a combination of statistical and comparative parameters, such as open reading frame (ORF) length, synonymous versus nonsynonymous base substitution rates, and similarity to known proteins (Badger and Olsen 1999;Frith et al 2006), indicates no significant coding potential, although it remains possible that small proteins or peptides are encoded within the transcript (Dinger et al 2008b).…”
Section: Sox2ot Transcripts and Locus Structurementioning
confidence: 99%